Mauritius Early Childhood Development : SABER Country Report 2012 - World Bank (Washington, DC, 2014)
This report presents an analysis of the early childhood development (ECD) programs and policies which affect young children in Mauritius. It is part of a series of reports prepared by the World Bank using the systems approach for better education results (SABER)-ECD framework and includes analysis of early learning, health, nutrition, and social and child protection policies and interventions in Mauritius, along with some regional and international comparisons. The Government of Mauritius (GoM) runs free public preschools, and gives cash transfers to private schools for every child enrolled. The GoM offers free public healthcare, including essential health and nutrition services for pregnant women and young children. While the GoM has implemented important ECD policies and programs, some aspects of the legal framework and systems to monitor and assure quality can be improved.